2003
DOI: 10.1097/01.ogx.0000068791.04785.8d
|View full text |Cite
|
Sign up to set email alerts
|

Common Complementary and Alternative Therapies for Yeast Vaginitis and Bacterial Vaginosis: A Systematic Review

Abstract: After completion of this article, the reader will be able to list the most common complementary and alternative medicine therapies for vaginitis, summarize the data surrounding the efficacy of each therapy, describe the adverse affects of each therapy, and outline which therapies are recommended and not recommended for vaginitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…Prolonged topical use can lead to allergic reactions or chemical burns. 59 No studies were found that examined the use of preparations of odourless garlic, either oral or intravaginal.…”
Section: Garlicmentioning
confidence: 98%
“…Prolonged topical use can lead to allergic reactions or chemical burns. 59 No studies were found that examined the use of preparations of odourless garlic, either oral or intravaginal.…”
Section: Garlicmentioning
confidence: 98%
“…Essential oils (EO) are complex mixtures of volatile compounds that result from secondary metabolic pathways of plants (Bakkali et al, 2008). They are considered valuable therapeutic alternatives to treat women suffering from vaginitis and vaginosis (Koroch et al, 2007;Palmeira de Oliveira et al, 2011;Van Kessel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, our collective knowledge of the etiology of BV and of treatment that best sustains normal, Lactobacillus-predominant vaginal flora remains grossly incomplete. When I speak to health-care providers around the country about BV, I am amazed at the depths of their resourcefulness in trying to find a treatment that helps their patients [8]resourcefulness that is probably directly related to their (not to mention their patients') desperation in failing to satisfactorily treat this condition.…”
mentioning
confidence: 98%